§ 2.

                  18.
U(x) V(x) ,
f(x) × U(x) + g(x)×V(x) = 1.

 

18.01.

f(x) = x2 + 3x 3,
g(x) = 2 3 + 1;

18.02.

f(x) = 2x2 2x 5,
g(x) = x2 1;

18.03.

f(x) = x2 5x + 4,
g(x) = 42 3 2;

18.04.

f(x) = 4x2 + x + 2,
g(x) = 2x2 + 3 2;

 

18.05.

f(x) = x2 x + 3,
g(x) = 22 3 3;

18.06.

f(x) = 2x2 + 3x + 2,
g(x) = x2 3 + 4;

 

18.07.

f(x) = 2x2 + 3x 4,
g(x) = 42 5 4;

18.08.

f(x) = 3x2 + 2,
g(x) = x2 5 + 1;

 

18.09.

f(x) = 4x2 + 1,
g(x) = 32 3;

18.10.

f(x) = 4x2 + 4x + 1,
g(x) = 3x2 3 3;

 

18.11.

f(x) = 4x2 2x + 2,
g(x) = 32 5 + 4;

18.12.

f(x) = 4x2 4x + 4,
g(x) = 3x2 4 + 2;

18.13.

f(x) = 3x2 + x 5, g(x) = 42 3 + 14;

18.14.

f(x) = 2x2 4x,
g(x) = 4x2 3 + 4;

18.15.

f(x) = x2 3x,
g(x) = 2 4 1;

18.16.

f(x) = 2x2 + x + 2,
g(x) = x2 + 2 5;

18.17.

f(x) = x2 4x + 3,
g(x) = 2 + 2 2;

18.18.

f(x) = 3x2 + 2x 2,
g(x) = 2x2 + 3;

18.19.

f(x) = 4x2 5x 5,
g(x) = 2 5 4;

18.20.

f(x) = 3x2 2,
g(x) = x2 3 + 3;

18.21.

f(x) = x2 4x 1,
g(x) = 2 2 + 2;

18.22.

f(x) = 3x2 4,
g(x) = x2 4 + 1;

18.23.

f(x) = 2x2 2x + 1,
g(x) = 32 + 2;

18.24.

f(x) = 2x2 + 2x 1,
g(x) = 2x2 4 + 5;

18.25.

f(x) = 3x2 + 5,
g(x) = 22 + 3 + 1;

18.26.

f(x) = x2 + 6x + 1,
g(x) = 3x2 + 4;

18.27.

f(x) = 2x2 + 5x 3,
g(x) = 22 4 + 2;

18.28.

f(x) = 3x2 + 6x + 5,
g(x) = x2 + 4;

18.29.

f(x) = x2 x + 3,
g(x) = 22 + 3;

18.30.

f(x) = x2 + 4x + 7,
g(x) = 2x2 5x;

 

18.31.

f(x) = 3x2 + x + 1,
g(x) = 42 + 2;

18.32.

f(x) = 3x2 x 2,
g(x) = x2 + 3x + 1;

 

18.33.

f(x) = x2 5x + 9,
g(x) = 22 + 7;

18.34.

f(x) = 4x2 x + 3,
g(x) = 3x2 + x 3;

 

18.35.

f(x) = 4x2 + 2x + 1,
g(x) = 2 + 4x + 2;

18.36.

f(x) = 3x2 3x + 4,
g(x) = 2x2 + 5.

 

 

\..\

                              Copyright © 2008-2009 ..   . .